Comunicação científica na era dos influenciadores digitais: o Youtube como ferramenta de difusão da ciência - MACHADO, Luis Fernando Pinheiro (2020)
A good idea and a camera in hand, may even be a cell phone, are prerequisites for those who want to gain space on the internet. In the scientific field, the digital medium has been shown as a new form of access to the democratization of knowledge. Therefore, this work addresses the potential of Youtube as a communication tool for scientific dissemination. The objects of study are the channels of the Manual do Mundo and Nerdologia, classified by the digital platform, as Science and Technology. Based on some concepts about journalism and scientific communication, the most visualized content was analyzed over the course of 12 months in 2018. It was sought to understand the level of scientific content present in the two channels, which currently total about 13 million registered users.